The Experience of Spirituality and Disability Sport for British Military Personnel Traumatically Injured in Iraq and Afghanistan: An Interpretative Phenomenological Analysis - Green, Sarah (Journal of disability & religion, 2014)
The aim of this article is to explore the spiritual experience of disability—sport—rehabilitation for British Service men and women who have sustained traumatic injuries as a consequence of combative warfare in Iraq and Afghanistan. At present, Great Britain's military-based initiative, called Battle Back uses disability sport as an integral part of its rehabilitation processes. However, there is a paucity of literature documenting the impact of disability sport, specifically around the spiritual experience of disability-sport-rehabilitation. The article draws upon data gathered from 11 semi-structured interviews with British Service personnel (nine male and two female), the transcripts of which were analyzed using interpretative phenomenological analysis (IPA). Three overarching themes emerged from interview discussion: (a) understandings of spirituality, (b) how disability sport helped to bring back life meaning and purpose, and (c) how the relationship between disability sport and spirituality might be framed in terms of goal striving and goal attainment. Findings indicate how participants used disability sport to re-enter their social worlds and how, as a consequence, they found renewed purpose and meaning in life.